Studi Sosio-Teologis Tentang Persekutuan Mahasiswa Happy Center Universitas Kristen Satya Wacana Sebagai Suatu Bentuk Gerakan Keagamaan - Maleachi Kameo (PAX HUMANA, 2019)
The religious movement in the form of student alliance is growing and had an influence on the religious life of students. This study aims to describe what are the factors and values in the development of a religious movement. Qualitative research with a descriptive approach and using interview techniques and direct observation in this study found that the actor who was the founder of the Happy Center fellowship was one of the factors that attracts and influences people in this case SWCU students to be involved in it. Through good acceptance, kinship, solidarity and supported by religious values based on Bible words are values that influence members of who are SWCU students to be actively involved in it. The Happy Center religious movement has become a place or space for students to live ecumenically or communally with various church differences and dedications from its members, but the fanatical attitude and exclusivity of this movement becomes isolated from the development of discourse and religious praxis.